Deskripsi Jenis Tindakan Operasi Pasien Bencana Gempa Bumi Lombok di RSUD Provinsi NTB Tahun 2018 - Hidayatullah, Audi; Namira, Hannah; fawwaz, muhfawwazkamal (Jurnal Kedokteran, 2019)
Background: After an earthquake occurs, local medical infrastructure often is damaged or destroyed. Planning, efficient allocation of resources, and an understanding of the types of injuries that might occur. Orthopedic surgeons an important role in providing care for earthquake victims. Long bone fractures, soft tissue injuries, limb injuries/fractures can survive with proper care. Therefore, after an earthquake it is very important to know what types of operations or actions are often needed in dealing with injuries after an earthquake, especially in the field of orthopedics. Method: This research is a retrospective descriptive study using medical records of patients affected by the Lombok earthquake. The sample size is determined by the consecutive sampling method. Samples were patients affected by the Lombok earthquake in 2018 who met the inclusion criteria in the Medical Record data at the Provincial General Hospital of West Nusa Tenggara in 2018. Result: In this study, there were 199 patients with a ratio of the number of men (49.2%) and women (50.8%). The most common types of operative actions were debridement 34.2%, ORIF 31.2%, craniotomy 13.1%, laparotomy 6.5%, debridement and ORIF 0.5%, WSD 2%, laminectomy 5%, skin graft and OREF respectively 1%, amputation, burrhole, and maxilla reconstruction were 0.5%. The highest classification of trauma is due to fracture 67.8%, head/intracranial trauma 14.7%, thoracic, abdominal/pelvic trauma 8.5%, crush injury and skin loss 1%, other trauma 7%. Conclusion: Variations in trauma injury and operative actions due to the Lombok earthquake require medical personnel, especially orthopedists, to properly handle trauma cases.